Are the Scandinavian Gods of Indo-European Heritage? - Liberman, Anatoly (Scandinavistica Vilnensis, 2014)
The origin of Germanic deities poses the question familiar from the study of phonemes, grammatical forms, and syntactic constructions: Indo-European heritage or local descent? Since from medieval Germania only Scandinavian mythology has come down to us, discussion centers around Othin, Thor, Týr, Baldr, etc. None of them has ascertainable roots in Indo-European, even when etymology points in that direction. Nor has George Dumézil succeeded in showing that the Indo-European and the Scandinavian pantheon, with their alleged tripartite division, are a good match, but from the nature of the case the question remains open.